The rural identity and the encroaching city: Governance, policy and development in Northern Virginia's Wine Country. (1st December 2019) - Cowell, Margaret; Eckerd, Adam; Smart, Henry
Abstract: In exurban areas, there are commonly issues and tensions associated with development and rural life. We assess how two counties located approximately one hour west of Washington, DC manage these tensions. Although both have enabled development, they have done so in different ways and neither has simply succumbed to exurban development as a given. Utilizing stakeholder interviews and document analysis, we note the different policy approaches that the two counties have taken and contrast them with the more common imagery of areas that fully acquiesce to suburban style development. Our findings suggest that tensions between the pressures of development and the persistent appeal of the rural identity occupy much time and attention in these two counties. Both counties have adopted observable policy changes driven by development pressures in recent years, underscoring a policy landscape that is in flux and the modern tension between the commercial economy of modernity, and the rural identity that is retained from the past. We observe that rural governance is largely about land, while urban governance is largely about people. As these two cases suggest, exurban governance has to be about both issues and this tension may lead to governance that is inherently unstable.